2014
DOI: 10.1007/s11906-014-0433-0
|View full text |Cite
|
Sign up to set email alerts
|

New Components of the Renin-Angiotensin System: Alamandine and the Mas-Related G Protein-Coupled Receptor D

Abstract: The renin-angiotensin system is an important component of the central and humoral mechanisms of blood pressure and hydro-electrolytic balance control. Angiotensin II is a key player of this system. Twenty-five years ago the first manuscripts describing the formation and actions of another peptide of the RAS, angiotensin-(1-7), were published. Since then several publications have shown that angiotensin-(1-7) is as pleiotropic as angiotensin II, influencing the functions of many organs and systems. The identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 49 publications
1
47
0
1
Order By: Relevance
“…5 It binds to MrgD receptors. 5,9, 10 The only difference between alamandine and Ang-(1-7) is the existence of an N-terminal alanine residue (Ala1) in alamandine. 5 Alamandine can be formed in the rat heart after perfusion with Ang-(1-7).…”
mentioning
confidence: 99%
“…5 It binds to MrgD receptors. 5,9, 10 The only difference between alamandine and Ang-(1-7) is the existence of an N-terminal alanine residue (Ala1) in alamandine. 5 Alamandine can be formed in the rat heart after perfusion with Ang-(1-7).…”
mentioning
confidence: 99%
“…Alamandine acts through binding to the receptor MrgD (Lautner et al 2013; Hrenak et al 2016; Etelvino et al 2014). In the present study, we found that MrgD expression was higher in the hearts of SHRs than those of WKY rats, and Ang II treatment increased MrgD levels in cardiomyocytes, which suggest that alamandine receptor activity is enhanced in the heart during hypertension and cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, Santos et al demonstrated that Ang-(1-7) is the ligand for the G-protein-coupled receptor Mas, and that the ACE2-Ang-(1-7)-Mas axis is the counter-regulating of the actions of classical RAS [4,5]. Also, a variety of biologically active peptides, novel components of the RAS have been found recently: proangiotensin-12 (angiotensin-(1-12)) [6], angiotensin A (Ang A) [7,8] and alamandine [9,10].…”
Section: Short Overview Of the Rasmentioning
confidence: 99%